Instructional material development using ontology learning / Khairul Nurmazianna Ismail, Fadzlin Ahmadon and Fadilah Ezlina Shahbudin - Ismail, Khairul Nurmazianna; Ahmadon, Fadzlin; Shahbudin, Fadilah Ezlina (Penerbit UiTM (UiTM Press), 2018)
In a university setting, lecturers are instructional designers responsible to design and develop instructional materials to be used in class. Textbooks and presentation slides are among the sources used in the delivery of knowledge. However, in order to facilitate different students’ learning styles, alternatives for textbooks must be considered, allowing the course content to be organised in smaller chunks. This paper describes the development ontology process using ontology learning technique. Ontology is a set of knowledge which contains objects, concepts, entities, and the relationships among them in a particular domain. In this study, the course chosen to analyse the development of ontology is Fundamentals of Computer Science (CSC401). This is an introductory course taken by students during semester one in the Faculty of Computer and Mathematical Sciences. Textbook is the source used in developing this ontology. The technique chosen in this study is a semi-automatic ontology development that can accelerate the process of producing a new ontology, while the development phases involved are the ‘extraction of important concepts’ and ‘representation of ontology’. The result shows that an ontology can be represented in the form of visual graph such as mind map. This matches the learning preference of visual learners and enrich their learning experiences.